IMPLEMENTASI PERJANJIAN REGIONAL ECONOMIC COMPREHENSIVE PARTNERSHIP TERHADAP PERDAGANGAN INDONESIA DENGAN NEGARA ANGGOTA TAHUN 2020-2023 - Fandy Ahmad Setia Budi (2023)
This study aims to determine the implementation of the Regional Comprehensive Economic Partnership (RCEP) agreement on trade between Indonesia and its member countries in 2020-2023. This study uses qualitative research. His research methods include data collection and data analysis. Data is collected through several literatures to obtain secondary data. The research framework used in this research is economic regionalism theory, implementation theory, FTA theory and FTA concept. The research results show that the agreement is implemented to provide uniformity of trade regulations which will encourage increased market access, market liberalization, and bring in more FDI. Even though it has a fairly large scale, RCEP does not eliminate other agreements that have been formed in the past between ASEAN members and externally. With the implementation of RCEP by Indonesia, PTA and FTA have proven beneficial for Indonesia in efforts to boost the economy and expand international trade markets, especially on the ASEAN+1 scale, where 92 percent of export tariffs have been eliminated. In addition, Indonesian business players will also benefit from the simplified Rules of Origin (RoO) as it provides flexibility to exploit market access advantages and benefits from RCEP's regional accumulation rules.